The influence of an up-front experiment on respondents' recording behaviour in payment diaries: Evidence from Germany - Susann Sieber; Tobias Schmidt (Deutsche Bundesbank, 2015)
In this paper, we analyse the recording behaviour of German consumers in a one week diary on their point-of-sales expenditures. We are particularly interested in the effect of a behavioural experiment, eliciting respondents' risk preferences, on their recording behaviour. In the experiment, run shortly before the consumers start to fill in the diary, the consumers have the choice between receiving a sure payment of 10 euro and participating in a game. If they opt for playing the game they roll a die and either win 20 euro or nothing. We ask whether respondents' recording behaviour differs depending on whether individuals who do roll the die lose or win. We argue that winners may attach a more positive feeling to the survey than losers and therefore exhibit more commitment to the diary, e.g. by reporting better quality data. Beyond providing evidence on the effect of conducting up-front experiments in representative surveys our results also contribute to the literature on incentives. For participants who roll the die, the experiment can be seen as a tool to randomly assign an incentive to respondents. Our results indicate that the outcome of the game has an impact on the quantity of transactions recorded, but does not affect other aspects of data quality. It also has a negligible impact on substantive measures like the cash share.
Keywords: C83; D12; E41; 330; incentives; risk experiments; payment diary; data quality